To solve the equation -7x - 2y = -13, we can follow these step-by-step answers:
Step 1: Start with the given equation: -7x - 2y = -13.
Step 2: To make things simpler, let's isolate the variable x by getting rid of the y-term. Since we want to eliminate the coefficient of y (-2y), we need to multiply the entire equation by the reciprocal of -2, which is -1/2. This is done to maintain the equation's balance.
Step 3: Multiply every term in the equation by -1/2:
-1/2 * (-7x) - 1/2 * (-2y) = -1/2 * (-13)
This simplifies to:
(7/2)x + y = 13/2
Step 4: Now the equation becomes (7/2)x + y = 13/2, which is in a more understandable form. Let's continue solving for x.
Step 5: To eliminate the y-term and isolate x, we can subtract y from both sides of the equation:
(7/2)x + y - y = 13/2 - y
This simplifies to:
(7/2)x = 13/2 - y
Step 6: Finally, to solve for x, we can multiply both sides of the equation by the reciprocal of (7/2), which is 2/7.
Step 7: Multiply both sides of the equation by 2/7:
(2/7) * (7/2)x = (2/7) * (13/2 - y)
This simplifies to:
x = (26/14) - (2y/7)
Step 8: Simplify further if needed:
x = 13/7 - (2y/7)
So, the solution to the equation -7x - 2y = -13 is x = 13/7 - (2y/7).
what are the step by step answers for solving
-7x-2y=-13
1 answer